O projecto doméstico. A evolução da terminologia do programa da casa - Diana Maria Pinho Neves (2012)
The concept of home and dwell is already a rich and assorted field ofstudy, forming one of the areas of greatest interest in architecture. In thisresearch we seek recognition of the program, in the context of domesticdesign, as an operational tool.Our research was concentrated on the development of a studyabout the transformation of the terminology of the program of the house,investigating the designations given to spaces that are or were part of thehousing project, in the portuguese context over the past centuries.With the goal of understanding the landscape of domestic program,we prepared a compilation of terms, made from the consultation of genericbibliography on domestic space and portuguese magazines of the twentiethcentury, specialized in architecture. This allowed a grouping of terms bycategories, linking them with foreign terms, which are the source of muchof the lexicon created.The work consists of two parts. In the first introductory part, weintend to make a contextualization of the domestic program, analyzingthe specificity of this instrument in the field of architecture and thefundamental aspects since its evolutionary character to the utility at thetime of conception of the architectural object.The body of work aims to dissect fragments and spaces of the house,presenting terms that constitute the domestic program and revealing theirnames and evolution. We seek to observe the domestic space as a territoryof multiple knowledges. This work is a compilation of ideas, opinions anddefinitions.